2013
DOI: 10.1111/gfl.12030
|View full text |Cite
|
Sign up to set email alerts
|

Deformation bands and their impact on fluid flow in sandstone reservoirs: the role of natural thickness variations

Abstract: Cataclastic deformation bands, which are common in sandstone reservoirs and which may negatively affect fluid flow, are generally associated with notable thickness variations. It has been suggested previously that such thickness variations represent an important control on how deformation bands affect fluid flow. The effects of such thickness variations are tested in this study though statistical analysis and fluid flow simulation of an array of cataclastic deformation bands in Cretaceous sandstones in in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 45 publications
1
25
0
2
Order By: Relevance
“…The reason for these differences is that the introduction of permeability heterogeneity in the models results in slower and more irregular waterfront propagation, compared to models where deformation bands are absent. Thus, at the local scale, deformation bands clearly affect flow patterns and the nature of waterfront propagation; similar finds were reported by Rotevatn et al (2013) for arrays of contractional deformation bands in porous siliciclastic rocks. Deformation band effects on the speed of flow Fachri et al (2013), based on flow simulations of larger-scale reservoir models of relay zones in siliciclastics with deformation band damage zones, reported a link between increasingly complex waterfront shapes (as a function of decreasing deformation band permeability) and a decrease in the speed at which fluid fronts propagate.…”
Section: Deformation Band Effects On the Nature Of Waterfront Propagasupporting
confidence: 83%
See 2 more Smart Citations
“…The reason for these differences is that the introduction of permeability heterogeneity in the models results in slower and more irregular waterfront propagation, compared to models where deformation bands are absent. Thus, at the local scale, deformation bands clearly affect flow patterns and the nature of waterfront propagation; similar finds were reported by Rotevatn et al (2013) for arrays of contractional deformation bands in porous siliciclastic rocks. Deformation band effects on the speed of flow Fachri et al (2013), based on flow simulations of larger-scale reservoir models of relay zones in siliciclastics with deformation band damage zones, reported a link between increasingly complex waterfront shapes (as a function of decreasing deformation band permeability) and a decrease in the speed at which fluid fronts propagate.…”
Section: Deformation Band Effects On the Nature Of Waterfront Propagasupporting
confidence: 83%
“…Similar variability has been shown for deformation bands in porous sandstones, and Torabi & Fossen (2009) argued that spatial variability of permeability or thickness within deformation bands may reduce their ability to retard flow. Rotevatn et al (2013) tested this assertion and demonstrated that the effects of such variability on aquifer-scale flow are limited; rather, deformation band connectivity as well as permeability contrast were identified as the most important controls on effective permeability and flow. Figure 4d shows a comparison of the relation between porosity and permeability in sandstone (data from Torabi et al 2013) and carbonate rocks (data from this study) both for host rock and deformation bands.…”
Section: Permeability Of Deformation Bands In Porous Carbonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many experiments on the water flow in fractured rocks had been carried out [1][2][3][24][25][26][27][28]. Specifically, Miao et al [1] analyzed the seepage properties of broken sandstone with different porosities; Ma et al [2,3] obtained the relationship between the permeability and variable grain diameters under variable axial displacements.…”
Section: Geofluidsmentioning
confidence: 99%
“…It is also well-established that deformation bands in porous sandstones may be associated with a bulk reduction in permeability in the range of 1e3 (occasionally up to six) orders of magnitude relative to host rock (e.g. Taylor and Pollard, 2000;Sternlof et al, 2004;Fossen et al, 2007;Rotevatn et al, 2008;Ballas et al, 2012;Rotevatn et al 2013); for pure compaction bands (sensu Mollema and Antonellini, 1996) in porous sandstones, up to 3 magnitude order permeability reductions have been reported Deng et al, 2015).…”
Section: Introductionmentioning
confidence: 98%